Assessing genetic diversity of Indonesian Andaliman (Zanthoxylum acanthopodium DC.) germplasm based on 7 RAPD markers - Putri, Lollie A.P; Sinaga, Ayu O.G; Sembiring, Indirani M.S; Sinaga, Ann (Proceeding International Conference on Global Resource Conservation, 2015)
This is the first publication on Zanthoxylum acanthopodium ofÂ Indonesian germplasm based on RAPD markers. We used 7 polymorphic RAPD markers in Z. acanthopodium DC to characterize 30 accessions from three district of Â North Sumatera, Indonesia. Our principal objectives are to study the genetic diversity ofÂ the genitors. The RAPD analyse was used with 7 random primers: OPH-06, OPC-12, OPN-03, OPN-09, OPD-13, OPI-20 and OPM-01. These seven primers showed 55 bands. Further genetic diversity coefficient and the phylogenetic dendogram were developed using the Darwin 5.05 software. The Principal Coordinates Analysis (PCoA) identifies, with axes 1 and 2 explaining 39.96 % of the total molecular variation. From the analysis of genetic distance and dendogram, 30 accessions of North Sumatraâs andaliman grouped into 3 clusters. This study showed high genetic dissimilarity inter origin and intra origin.Keywords:Â Genetic diversity; North Sumatera; RAPD marker; Zanthoxylum acanthopodium